Individualization of Hematopoietic Stem Cell Transplantation Using Alpha/Beta T-Cell Depletion - Rådestad, Emelie; Sundin, Mikael; Törlén, Johan; Thunberg, Sarah; Önfelt, Björn; Ljungman, Per; Watz, Emma; Mattsson, Jonas; Uhlin, Michael (Frontiers in Immunology, 2019)
Allogeneic hematopoietic stem cell transplantation (HSCT) is associated with several potentially lethal complications. Higher levels of CD3+ T cells in the graft have been associated with increased risk of graft-versus-host-disease (GVHD), but also beneficial graft-versus-leukemia and reduced infections. To tackle post-transplant complications, donor lymphocyte infusions have been used but with increased risk of GVHD. To reduce this risk, we performed depletion of αβ T-cells and treated 12 patients post-HSCT suffering from infections and/or poor immune reconstitution. The αβ T-cell depleted cell products were characterized by flow cytometry. The median log depletion of αβ T-cells was -4.3 and the median yield of γδ T-cells was 73.5%. The median CD34+ cell dose was 4.4×106/kg. All 12 patients were alive 3 months after infusion and after 1 year, two patients had died. No infusion-related side effects were reported and no severe acute GVHD (grade III-IV) developed in any patient post-infusion. Overall, 3 months after infusion 11 out of 12 patients had increased levels of platelets and/or granulocytes. In conclusion, we describe the use of αβ T cell depleted products as stem cell boosters with encouraging results.